Sosialisasi dan Pelatihan Content Marketing Berbasis Digital Untuk Meningkatkan Daya Saing UMKM - Edy Purwanto; M. Munir Syam AR; Miftahol Arifin (LPMP Imperium, 2023)
The use of digital marketing is currently one of the keys to the success of MSMEs. The activity of marketing a product via the internet can certainly reach consumers who cannot be reached by conventional marketing. The use of social media such as Instagram, Facebook and others will certainly make it easier for the message to be conveyed to consumers. MSMEs must have the ability to create content marketing. In Pagerungan Besar village itself there are several MSMEs that have products that are quite well known. However, there are problems in the marketing sector, especially creating content marketing. This activity was carried out to provide education to MSME players and provide training on procedures for creating digital-based content marketing. The activities carried out are in the form of outreach and training. This method is deemed appropriate for solving the problems experienced by MSMEs. The stages in this activity are the preparation stage, implementation stage and also the activity evaluation stage. From this activity, information was obtained that there was an increase in participants' understanding of content marketing. Next, it is necessary to provide assistance in creating attractive packaging designs that meet the established standards.